Hybrid Experimental Approaches in Facade Thermal Performance Research: A Systematic Review - Rizki Fitria Madina; Surjamanto Wonorahardjo; Dewi Larasati; Indah Widiastuti (Jurnal Lingkungan Binaan Indonesia, 2025)
Building façades significantly influence building thermal performance and contribute to urban heat mitigation, particularly in hot-humid climates. While field testing, laboratory experiments, numerical modeling, and digital simulations are widely applied in façade research, methodological frameworks for integrating these into hybrid approaches remain limited. This study systematically reviews 32 peer-reviewed articles to analyze the types, sequencing, and disciplinary tendencies in applying hybrid experimental approaches for façade thermal performance research. Seven type of hybrid experimental approach were identified, with combination of field experiments-simulations are most common. Stage sequencing varied by research objectives, while disciplinary background influenced whether studies began with modelling or empirical experimentation. The proposed hybrid experimental research framework offers strategic guidance for approach selection and sequencing, supporting resource efficiency and methodological rigor in sustainable building design.